Receipt of Substance Use Counseling Among Ambulatory Patients Prescribed Opioids in the United States - Kirk E Evoy; Charles E Leonard; Jordan R Covvey; Leslie Ochs; Alyssa M Peckham; Samantha Soprano; Kelly R Reveles (SAGE Publishing, 2020)
Background: As opioid-related overdose deaths climb in the U.S., risk reduction measures are increasingly important. One such measure recommended involves provision of proactive substance use counseling regarding the risks of opioid analgesics. This is particularly important in patients at increased risk of overdose, such as those with substance use disorders (SUD) or those receiving concomitant medications that further increase the overdose risk (eg, benzodiazepines, gabapentinoids, or Z-hypnotics). However, previous research regarding the likelihood that such counseling is provided during outpatient prescriber visits is lacking. Objectives: To determine the percentage of U.S. ambulatory care visits in which patients taking prescription opioids received substance use counseling, and whether counseling was more common in patients with concomitant GABAergic medication(s) (benzodiazepine, gabapentinoid or Z-hypnotic) or substance use disorder (SUD) diagnosis. Methods: A cross-sectional analysis was conducted of all patients aged ⩾18 years identified as having a prescription opioid on their medication list within the 2014-2015 National Ambulatory Medical Care Survey data. Results: Among 162.7 million visits in which patients were taking opioid medication(s), substance use counseling was provided in 2.4%. During visits for patients receiving opioid(s) plus GABAergic(s), substance use counseling was marginally more common (3.1% versus 2.0%, P < .0001). Substance use counseling was also more common among visits for patients taking opioid(s) with SUD (18.9% versus 1.5%, P < .0001). Among visits in which a patient was diagnosed with SUD and taking opioid(s) plus GABAergic(s), counseling was more common (23.1% versus 1.4%, P < .0001) compared to patients taking opioid(s) plus GABAergic(s) without SUD. Conclusions: Among national ambulatory care visits in the United States, substance use counseling is provided infrequently for patients taking opioids, even when significant risk factors are present. Increasing patient education may help reduce opioid-related overdose mortality.